Performance of youth entrepreneurs in Malaysia micro small and medium enterprises - Mohd Khan, Shazida Jan; Md Noor, Nur Syamilah; Anuar, Abdul Rahim (EconJournals, 2016)
This study aim to look on the role of government policy, infrastructure, and business support facility towards the performance of youth entrepreneurs involved in micro small and medium enterprises (SMEs) in Malaysia. Entrepreneurship development calls for support from various quarters and primarily the need exists to initiate a youth entrepreneurship culture and drive amongst the youth in the society. The study adopts a quantitative approach whereby a questionnaire survey was used to gather data. Seemingly unrelated regression was chosen as a method of analysis and the result of this study is expected to give insight into the existing government policy, infrastructure, and business support facility while assisting in formulation policies for the development of youth entrepreneur specifically involved in micro SMEs